The Lost Art of Scripture : Rescuing the Sacred Texts - Armstrong, Karen (London The Bodley Head, 2019)
In our increasingly secular world, holy texts are at best seen as irrelevant, and at worst as an excuse to incite violence, hatred and division.
Include Bibliography and Index
Keywords: Religions -- Religion and culture